Two new species of Cumacea (Malacostraca, Peracarida) from Peter The Great Bay (Sea of Japan) - Tzareva, Ludmila; Vassilenko, Stella (Zootaxa, 2006)
Cumacean material, collected in Peter the Great Bay (Sea of Japan), near Furugelm and Bolshoy Pelis Islands at the depths of 3–17 m, was investigated. Two new species inhabiting sublittoral zone were found and are described in this work as Lamprops tenuis sp. nov. and Bodotria furugelmiensis sp. nov.